In-plane behavior of cavity masonry infills and strengthening with textile reinforced mortar. (1st February 2018) - Akhoundi, Farhad; Vasconcelos, Graça; Lourenço, Paulo; Silva, Luis M.; Cunha, Fernando; Fangueiro, Raúl
Highlights: In-plane behavior of masonry infilled reinforced concrete frames that were typical construction of south European countries in 1980 were investigated. Strengthening technique based on textile reinforced mortar technique (TRM) by using two different textile meshes was used to improve the in-plane behavior of this kind of structures. TRM technique improves the in-plane response of infilled frames and works as damage concentrator. Abstract: The seismic vulnerability of masonry infilled reinforced concrete (rc) frames observed during past earthquakes in some south European countries resulted in losses of human lives and huge repair or reconstruction costs, justifies the need of deeper study of the seismic behavior of masonry infills enclosed in rc frames. Therefore, the main goals of this study are related to: (1) better understanding of the cyclic in-plane behavior of traditional brick infills built in the past decades as enclosures in rc buildings in Portugal; (2) analysis of a strengthening technique based on textile reinforced mortar (TRM) aiming at enhancing the in-plane behavior. To accomplish the objectives, an extensive experimental campaign based on in-plane static cyclic tests on seven reduced scale rc frames with masonry infill walls was carried out. The performance of strengthening of masonry infill based on textile reinforced mortar was also evaluated experimentally. Among the conclusions of this research, it should be stressed that: (1) the presence of infill inside the bare frame could significantly enhance the in-plane stiffness and resistance of bare frame; (2) TRM technique could enhance the in-plane behavior of infilled frames by improving the lateral strength and by reducing significantly the damage of the brick infill walls.